2016
DOI: 10.1088/0741-3335/58/12/124005
|View full text |Cite
|
Sign up to set email alerts
|

Resistive sensor and electromagnetic actuator for feedback stabilization of liquid metal walls in fusion reactors

Abstract: Liquid metal walls in fusion reactors will be subject to instabilities, turbulence, induced currents, error fields and temperature gradients that will make them locally bulge, thus entering in contact with the plasma, or deplete, hence exposing the underlying solid substrate. To prevent this, research has begun to actively stabilize static or flowing free-surface liquid metal layers by locally applying forces in feedback with thickness measurements. Here we present resistive sensors of liquid metal thickness a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Embedded in the container are 3×4 copper electrodes of 2 mm diameter and various lengths, for comparison (1,16 and 25 mm, each with its own advantages and disadvantages 14 ). Adjacent electrodes are spaced by 25 mm in one direction and 15 mm in the other.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Embedded in the container are 3×4 copper electrodes of 2 mm diameter and various lengths, for comparison (1,16 and 25 mm, each with its own advantages and disadvantages 14 ). Adjacent electrodes are spaced by 25 mm in one direction and 15 mm in the other.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work 14 we had shown that, quite simply, and on the net of small corrections, the electrical conduca) fvolpe@columbia.edu tance between two electrodes immersed in the LM scales linearly with the local LM thickness. Resistive measurements were used to infer the LM thickness in a single location and at a single time 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, free-surface liquid metal (LM) layers will tend to be uneven [9] as a result of nonuniform force fields, liquid metal instabilities and turbulence [10]. Uneven LM surfaces could enter in contact with the plasma, contaminate it, cool it, and possibly disrupt it, or they might expose the underlying solid wall to damage by heat and neutrons, and expose the plasma to a material with less benign erosion and wall recycling properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the j × B force-density will change, and adjustments of the applied current-pattern might be required, in feedback with multi-point measurements of liquid metal thickness. This is the subject of separate works [10,11].…”
Section: Introductionmentioning
confidence: 99%